Analytical study of reduced beam sections under monotonic load - Casita, Cintantya Budi; Kamandang, Zetta Rasullia (IPTEK Journal of Proceedings Series, 2018)
This paper presents the result of three different type of reduced beam sections (RBS): radius cut, straight cut, and tapered cut under monotonic load using finite element analysis. Load is applied monotonically and divided into 9 steps, start from 500 N to 4500 N, which increasing 500 N for each step, continuously. The dimension for the beam is WF 500x200x10x16 is used for those three types of RBS. The results show that radius cut gives better performance than the other two types. Stress distribution, load-stress curve, and load-displacement curve of those three types of RBS are compared as the result, then lead to the conclusion that the most effective connection amongst those three types of RBS above is RBS with Radius Cut.